NITROGEN ASSIMILATION AND THE CONTROL OF AMMONIUM AND NITRATE ABSORPTION BY MAIZE ROOTS - Lee, R; Purves, J; Ratcliffe, R; Saker, L (1992)
Experimental treatments designed to affect the pathway of nitrogen assimilation were applied to the roots of intact maize plants growing with ammonium or nitrate as N-sources. The treatments comprised: external amino acid feeding; specific inhibitors of GS, GOGAT, and aminotransferases; and N-starvation. Their actions in vivo were confirmed by 14N- or 15N-NMR spectroscopy, or by HPLC analysis of tissue extracts. A strong correlation was noted between the levels of glutamine and asparagine in the roots.Rates of ammonium and nitrate absorption by the plants were then measured, over both short (5 min) and longer (1.5 h) periods. The results fell into two classes. After treatments which raised the intracellular concentrations of glutamine and/or asparagine, net uptake of N was suppressed, while conditions which decreased root glutamine and/or asparagine, stimulated net uptake of N. These findings are discussed in relation to the control of N-absorption during growth with differing levels of nitrogen supply. © 1992 Oxford University Press.